Host genetics contributes to the effectiveness of dendritic cell-based HIV immunotherapy. Issue 8 (3rd August 2018) - Reis, Edione C.; da Silva, Lais T.; da Silva, Wanessa C.; Rios, Alexandre; Duarte, Alberto J.; Oshiro, Telma M.; Crovella, Sergio; Pontillo, Alessandra
ABSTRACT: Systems biological analysis has recently revealed how innate immune variants as well as gut microbiota impact the individual response to immunization. HIV-infected (HIV+) patients have a worse response rate after standard vaccinations, possibly due to the immune exhaustion, increased gut permeability and microbial translocation. In the last decade, dendritic cells (DC)-based immunotherapy has been proposed as an alternative approach to control HIV plasma viral load, however clinical trials showed a heterogeneity of immunization response. Hypothesizing that host genetics may importantly affects the outcome of immunotherapy in HIV+ patients, genetic polymorphisms' distribution and gene expression modulation were analyzed in a phase I/II clinical trial of DC-based immunotherapy according to immunization response, and quality of vaccine product (DC). Polymorphisms in genes previously associated with progression of HIV infection to AIDS (i.e.: PARD3B, CCL5) contribute to a better response to immunotherapy in HIV+ individuals, possibly through a systemic effect on host immune system, but also directly on vaccine product. Genes expression profile after immunization correlates with different degrees of immune chronic activation/exhaustion of HIV+ patients (i.e. PD1, IL7RA, EOMES ), but also with anti-viral response and DC quality (i.e.: APOBEC3G, IL8, PPIA ), suggested that an immunocompetent individual would have a better vaccine response. These findings showed once more that host genetics can affect the response to DC-based immunotherapy in HIV+ individuals, contributing to the heterogeneity of response observed in concluded trials; and it can be used as predictor of immunization success.